EPIDEMIOLOGY OF METHICILLIN RESISTANT STAPHYLOCOCCUS AUREUS IN ARAB COUNTRIES OF THE MIDDLE EAST AND NORTH AFRICAN REGION - Hussam Tabaja; Joya-Rita Hindy; Souha S. Kan (Mediterranean Journal of Hematology and Infectious Diseases)
Available data suggests a high burden of methicillin-resistant staphylococcus aureus (MRSA) in Arab countries of the Middle East and North Africa (MENA). To review the MRSA prevalence and molecular epidemiology in this region, we used PubMed search engine to identify relative articles published from January 2005 to December 2019. Great heterogeneity in reported rates was expectedly seen. Nasal MRSA colonization ranged from 0-32% in healthy volunteers but 4-73% in healthcare workers. Infective MRSA rates ranged between 6%-66% in Saudi Arabia, 12%-29% in United Arab of Emirates, 13%-21% in Qatar, 14%-37% in Oman, 20%-72% in Lebanon, 56% in Gaza, 32%-68% in Jordan, 34%-88% in Iraq and Iraqi Kurdistan, 47%-77% in Egypt, 19-86% in Algeria, and 18-40% in Tunisia. In the GCC, [PVL-] ST239-III, [PVL+] ST80-IV, [PVL+] ST30-IV, [PVL-] ST22-IV and its [PVL+] and [tst1+] variants, [PVL-] CC6-IV, [PVL-] CC5-IV, and [PVL-] ST5-II had a significant presence. In the Levant region, [PVL+] ST80-IV, [PVL+] ST30-IV, [PVL-] ST239-III, [PVL-] ST22-IV were prevalent in Lebanon, Jordan, and Gaza; [PVL-] ST22-IVa-t223 (“Gaza strain”) was prevalent in Gaza and Jordan; USA300, and USA800 were prevalent in Iraq. In North Africa, [PVL+] ST80-IV and [PVL-] ST239-III was commonly reported in Egypt, Algeria, and Tunisia. Finally, significant antimicrobial resistance was seen in the region with variation in patterns depending on location and clonal type. For a more accurate assessment of MRSA epidemiology and burden, the Arab countries need to implement national surveillance systems.